Potentials and technical implications of tag based and AI enabled optical real-time location systems (RTLS) for manufacturing use cases. Issue 1 (2022) - Thiede, Sebastian; Ghafoorpoor, Poorya; Sullivan, Brendan P.; Bienia, Sebastian; Demes, Michael; Dröder, Klaus
Abstract: Utilizing real-time position information of individual factory objects is a promising field of action in manufacturing systems. For realizing that, different types of real-time locating systems (RTLS) are available which differ according their inherent characteristics, performance and, thus, their feasibility for value adding manufacturing use cases. The paper introduces an innovative RTLS which utilizes optical AI enhanced sensors to detect and track objects. Detailed technical analyses also in comparison with established tag based ultra-wideband (UWB) RTLS underline the general feasibility and good performance. Finally, the capability profiles of those different RTLS technologies were brought together with the requirements of specific manufacturing use cases in order to derive favourable application fields.